0511 Health Benefits to Peers Participating in a Mentoring program for Treatment Adherence in Patients with Sleep Apnea. (12th April 2019) - Patel, Salma I; Wendel, Christopher; Berryhill, Sarah; Provencio, Natalie; DeArmond, Richard; Quan, Stuart F; Combs, Daniel; Skrepnek, Grant H; Parthasarathy, Sairam
Abstract: Introduction: Peer support aimed at improving treatment adherence can be effective in many chronic medical conditions including obstructive sleep apnea (OSA). Whether such peer-participation has any benefits to the well-being of peer-mentors who administer such peer support in unclear. We aimed to determine whether peers (who promote adherence to continuous positive airway pressure [CPAP] therapy in CPAP naïve patients with OSA) experienced any change in CPAP adherence, self-reported sleepiness, or health-related quality of life (HR-QOL). A secondary aim was to determine whether there was a "dose-effect" relationship between the number of CPAP naïve patients assigned to peer mentors and health benefits. Methods: We administered questionnaires to peer mentors at baseline and two-years following participation in a randomized controlled trial of peer support aimed at promoting adherence to CPAP therapy in treatment naïve patients with OSA. CPAP adherence of the peer-mentor was downloaded at the start and end of study participation. Results: Fifty four peer mentors participated in a trial that randomized 263 CPAP naive patients with OSA to peer-support versus attention-control. Peers (aged 57.4 ± 12.0 years; 50% women) were predominantly white with 15% Hispanic ethnicity. Of the peer mentors who were assigned participants (n=23), CPAP adherence (usage > 4 hours/night) did not change from baseline (93.1 ± 12.1%) to end of study participation (90.9 ± 16.1% P=0.57); vigilance subdomain of the Functional Outcomes Sleep Questionnaire (FOSQ) improved from 3.5 ± 0.55 to 3.8 ± 0.33 (P=0.04); global FOSQ scores and Epworth sleepiness scores tended to improve 18.1 ± 2.2 to 18.7 ± 1.7 (P=0.13) and 6.4 ± 5.0 to 5.2 ± 3.7 (P=0.14), respectively. The number of assigned CPAP naive patients to peer mentors was positively correlated with Global FOSQ score (beta= 0.42; P=0.011) and negatively correlated with Epworth sleepiness score (beta = - 0.60; P=0.046). Conclusion: Peer-mentors experienced health benefits to sleepiness and health-related quality of life by participating in a peer-support program with a dose-effect relationship based upon number of assigned mentees. Support (If Any): IHS-1306-02505 and HL138377